LEXICO-SEMANTIC AND LINGUACULTURAL FEATURES OF THE ENGLISH AND UZBEK COOKING UTENSILS - Mamatkulova Fotima Ashirkulovna (Web of Journals Publishing, 2024)
In this article English and Uzbek vocabulary related to cooking utensils are researched. The functioning of units at various levels that correspond to the English language's hyponymic category—including lexemes connected to the "cooking utensils" thematic group—is the focus of our study. One-word and composite nominations that are part of the defined system are the subject of this study. They were taken from text sources and explanatory, cultural, phraseological, and etymological dictionaries using continuous and representative sample collection.
Keywords: Linguacultural, feature, cooking utensils, tableware, hyperonym, dictionary, English, Uzbek.